The Use of Discovery-Based Learning to Encourage Students’ Motivation in Classroom - Widana, I Kadek Wahyu; Handayani, Made Sonia (The Art of Teaching English as a Foreign Language (TATEFL), 2022)
The students’ motivation in learning English is very important, due to English language mastery. Besides, the teacher needs an effective learning method, to encourage the students’ motivation in the learning process. This research aims to analyze the use of Discovery-based Learning to encourage students’ activeness in the classroom. This research was an experiment. The instrument used in this study were observation sheet and motivation questionnaire. The results of this research showed that the use of discovery-based learning in the classroom is very effective to engage the learners’ motivation to participate actively in the classroom. The mean score of motivation is achieved in posttest (4.17) compared to pretest (3.81). From the result of t test, the value of Sig. (2-tailed) is .041 which is lower than .05. The application of discovery-based learning is focused on student-centered activity, so that the learners can be more active in the learning process. In other words, the application of discovery-based learning is very appropriate to encourage the students’ motivation to participate actively in the classroom.